2006
DOI: 10.1186/1477-7525-4-74
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility of routine cataract surgery

Abstract: BackgroundIf decisions on health care spending are to be as rational and objective as possible, knowledge on cost-effectiveness of routine care is essential. Our aim, therefore, was to evaluate the cost-utility of routine cataract surgery in a real-world setting.MethodsProspective assessment of health-related quality of life (HRQoL) of patients undergoing cataract surgery. 219 patients (mean (SD) age 71 (11) years) entering cataract surgery (in 87 only first eye operated, in 73 both eyes operated, in 59 first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 31 publications
5
33
2
Order By: Relevance
“…The lack of change has been attributed either to lack of sensitivity of the HRQoL instrument used or to a lack of importance of vision in the overall perception of health. 5,6 Neither of these interpretations are supported in the current study, where improvements in perception of health were observed using a brief and simple instrument (Euroqol). The severe levels of pre-operative bilateral vision loss, more common in low compared to high income settings, may partially explain this difference.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…The lack of change has been attributed either to lack of sensitivity of the HRQoL instrument used or to a lack of importance of vision in the overall perception of health. 5,6 Neither of these interpretations are supported in the current study, where improvements in perception of health were observed using a brief and simple instrument (Euroqol). The severe levels of pre-operative bilateral vision loss, more common in low compared to high income settings, may partially explain this difference.…”
Section: Discussioncontrasting
confidence: 58%
“…3 Other studies using the SF-36 instrument have found improvements in some, 9 but not all, domains. 6,32 In contrast, several studies have found no evidence of significant change in generic HRQoL, 4,5,33,34 including self-rated health 6 following cataract surgery. The lack of change has been attributed either to lack of sensitivity of the HRQoL instrument used or to a lack of importance of vision in the overall perception of health.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Several previous studies have assessed the cost-utility of cataract surgery [8][9][10][11][12][13]. In the US, Busbee et al [8] reported that the costutility of first eye cataract surgery was $2,020/QALY and concluded that initial cataract surgery was highly costeffective when compared with procedures across multiple medical specialties.…”
Section: Introductionmentioning
confidence: 99%
“…Räsänen et al. () used the 15D instrument and reported an insignificant improvement in the mean 15D score, as only seeing of the 15 dimensions of the HRQoL instrument improved compared with baseline. Using the same generic instrument, 15D, we found slightly more improvement in the mean 15D score at 12 months with 0.018 in the present study versus 0.010 at 6 months after cataract surgery as found in the Räsänen et al.…”
Section: Discussionmentioning
confidence: 99%